2013
DOI: 10.1007/s10826-013-9807-1
|View full text |Cite|
|
Sign up to set email alerts
|

Parenting Stress, Social Support, and Depression for Ethnic Minority Adolescent Mothers: Impact on Child Development

Abstract: Rates of teenage pregnancies are higher for African American and Latina adolescents compared to their White peers. African American and Latina adolescent mothers also experience more adversities than their White peers, such as higher rates of depression, school dropout, and economic disadvantage. Furthermore, children of adolescent mothers are at higher risk for adverse development. Parenting stress and social support can impact outcomes experienced by adolescent parents and their children. The present study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
121
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(145 citation statements)
references
References 47 publications
10
121
2
5
Order By: Relevance
“…Previous studies suggested that associations between child developmental delay and maternal age could be explained by socio-economic status, parenting behavior and home environment [22,34,35], and maternal depression [7]. In our study, those maternal associated factors were not significantly different between adolescent and adult mothers.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previous studies suggested that associations between child developmental delay and maternal age could be explained by socio-economic status, parenting behavior and home environment [22,34,35], and maternal depression [7]. In our study, those maternal associated factors were not significantly different between adolescent and adult mothers.…”
Section: Discussioncontrasting
confidence: 55%
“…Maternal psychological distress during pregnancy is known to affect behavioral, cognitive, socio-emotional, and psychomotor development of infants, while postpartum distress is known to contribute to cognitive and socio-emotional development [6]. In addition, depression in pregnant adolescents was also found to be associated with higher developmental delays in infants [7].…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] DULCE accelerated access to concrete supports for newborns and their families; intervention families received greater support for their concrete needs during the infants' first 6 months of life. Previous research suggests that the early provision of concrete support may protect against child neglect and abuse and reduce parental stress, 46 and promote the formation of positive attachment relationships. 47,48 Other programs to address the concrete needs of families through improvements in primary health care have been described: WE CARE features a simplified, selfadministered needs assessment coupled with practice guidance to specific resources.…”
Section: Discussionmentioning
confidence: 99%
“…Parenting stress is defined as distress and uncomfortable experiences occurring in the process of carrying out the role of parenting [10]. It is the cause of emotional distress in marital life [11] and has been reported to be a predictor variable that negatively influences children's development [12]. Moreover, if parenting stress is high and for an extended period of time, the chance of experiencing depression increases, and because parental depression not only makes the relationship with children negative but also increases problem behaviors and negative emotions in children, it can be a conclusive factor that decreases the perceived happiness of children as a result [13].…”
Section: Introductionmentioning
confidence: 99%